2020
DOI: 10.1136/bmjopen-2019-033520
|View full text |Cite
|
Sign up to set email alerts
|

Usual care and a self-management support programme versus usual care and a relaxation programme for people living with chronic headache disorders: a randomised controlled trial protocol (CHESS)

Abstract: IntroductionChronic headaches are poorly diagnosed and managed and can be exacerbated by medication overuse. There is insufficient evidence on the non-pharmacological approaches to helping people living with chronic headaches.Methods and analysisChronic Headache Education and Self-management Study is a pragmatic randomised controlled trial to test the effectiveness and cost-effectiveness of a self-management education support programme on top of usual care for patients with chronic headaches against a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…In total, 150 papers were included [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsunclassified
“…In total, 150 papers were included [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsunclassified
“…We recruited 131 people: 130, 115 (88%) and 103 (79%) questionnaires were completed at baseline, 2 and 12 weeks, respectively (Table 1) (11).…”
Section: Resultsmentioning
confidence: 99%
“…The Chronic Headache Education and Self-Management Study (CHESS) is a programme grant funded by the UK's National Institute for Health Research (RP-PG-1212-20018) to test the effectiveness of a supportive self-management intervention for people living with chronic headache disorders (11). This current work forms part of the feasibility study, reported elsewhere (January 2016 to April 2017) (Black Country Research Ethics Committee (15/WM/0165)) (12).…”
Section: Methodsmentioning
confidence: 99%
“…Обсуждение. МИГБ является наиболее тяжелой формой хронической ежедневной головной боли, которая формируется на фоне избыточного употребления препаратов для купирования приступов головной боли [8][9][10][11][12].…”
Section: Assessment Of the Impact Of Headache On The Quality Of Life Using Halt At Baseline And 12-months Follow-up м±σunclassified